Emerging Perovskite Solar Cell Technology: Remedial Actions for the Foremost Challenges (Adv. Energy Mater. 42/2021). Issue 42 (11th November 2021) - Sahare, Sanjay; Pham, Hong Duc; Angmo, Dechan; Ghoderao, Prachi; MacLeod, Jennifer; Khan, Sadaf Bashir; Lee, Shern‐Long; Singh, Samareandra P.; Sonar, Prashant
Abstract : Perovskite Solar Cells In article number 2101085, Shern‐Long Lee, Samareandra P. Singh, Prashant Sonar and co‐workers review the foremost challenges facing perovskite solar cells (PSCs) research, and provide advanced remedial solutions including innovative light‐harvesting perovskites, advanced interfacial layers, device engineering, and encapsulation of the devices. These remedies and strategies may help researchers to select the appropriate methods and design their experiments to obtain high photo‐conversion efficiency in PSCs for commercial solar cell development.